Spontaneous Rupture of Spleen: A Case Report. - Singhal BM; Shakya P; Sagar S; Kaval S (Department of Surgery, UKM Medical Centre, 2014)
Spontaneous or idiopathic splenic rupture is a rare cause of acute abdominal pain and hemoperitoneum and its incidence is 1% of all cases of splenic rupture. The etiology of spontaneous splenic rupture can be idiopathic or it may occur as a complication of an infectious, neoplastic or hematologic disease. Splenic rupture presents with pain in the left upper quadrant with shock and features of peritoneal irritation, like Kehr’s sign (left shoulder pain due to diaphragmatic irritation) and Balance sign (palpable tender mass in left upper abdomen). The diagnosis of spontaneous splenic rupture presents a diagnostic challenge due to the absence of a history of trauma. Focused Abdominal Sonography for Trauma FAST may be suggestive but due to its limitations, Computerized Tomography Scan CT scan of abdomen is the best imaging modality both for detection and grading of splenic injury. Management can be non-operative or surgical depending on grade and hemodynamic status of the patient. We report a rare case of spontaneous rupture of the spleen, which was idiopathic and fulfills the criteria of Orloff and Peskin, due to absence of any history of trauma, absence of perisplenic adhesions or scarring, and it without any evidence of disease affecting the spleen with macro and microscopically normal spleen. This case also adheres to fifth criteria described by Crate and Payne, as there was no immunological evidence suggestive of any viral infections affecting the spleen.